(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
The objective of the present study was to develop more retentive and effective drug delivery system for mupirocin. The research was going on in achieving effective formulation. Mupirocin is an anti-microbial agent that is used in wounds healing treatment. First Screening of oil, surfactant and co-surfactant for SEDDS carried out. Solubility of drug was investigated in different oils, surfactant and co-surfactants by UV method. A drug was dissolved in available oil in which it exhibited maximum solubility, then surfactant and co-surfactant were added in which drug showed maximum solubility, mixed well on a magnetic stirrer. Transparent SEDDS were formed. Carbopol 940 and Polyacrylate sodium gelling agent was suspended in water and hydrated for overnight separately. For preparation of Emulgel, various ratios of gel and SEDDS were set. Emulgel was evaluated for %drug release, pH, and drug content. The results indicated that Emulgel gave better controlled release. The formulation F11 showed 99.27 percent drug release, pH 6.7 ± 0.1 and drug content 99.4 ± 0.11%. Formulation F11 was selected as an optimized formulation. The formulations of Emulgel delivered very good therapeutic efficacy for topical application.